Opis przypadkuAnomalous musculoskeletal morphology of anterior chest wall: a case report - Das, Srijit; Paul, Shipra; Mandal, Ashish Kumar (Archives of Medical Science, 2006)
The combination of rectus sternalis muscle, anomalous attachment of pectoralis minor muscle and supernumerary ribs in a single individual has not been reported by any research study, to the best of our knowledge. We report a left-sided rectus sternalis muscle, altered attachment pattern of the pectoralis minor muscle and the presence of a right-sided supernumerary rib in the third intercostal space of a 42-year-old male cadaver. Anatomical knowledge of rectus sternalis muscle may be important for radiologists who may misinterpret it to be a bulging mass in routine mammography and for surgeons performing reconstructive surgery. Variations of pectoralis minor muscle may influence the kinematics around the scapula and may be important for biomechanical studies. The shadow of the supernumerary rib may overlap and confuse radiologists interpreting roentgenograms. The aim of the study was to highlight the complex musculoskeletal defects and discuss their academic and clinical significance.